Priming potato plants with melatonin protects stolon formation under delayed salt stress by maintaining the photochemical function of photosystem II, ionic homeostasis and activating the antioxidant system - Efimova, Marina V.; Danilova, Elena D.; Zlobin, Ilya E.; Kolomeichuk, Liliya V.; Murgan, Olga K.; Boyko, Ekaterina V.; Kuznetsov, Vladimir V. (International journal of molecular sciences)
Melatonin is among one of the promising agents able to protect agricultural plants from the adverse action of different stressors, including salinity. We aimed to investigate the effects of melatonin priming (0.1, 1.0 and 10 µM) on salt-stressed potato plants (125 mM NaCl), by studying the growth parameters, photochemical activity of photosystem II, water status, ion content and antioxidant system activity. Melatonin as a pleiotropic signaling molecule was found to decrease the negative effect of salt stress on stolon formation, tissue water content and ion status without a significant effect on the expression of Na+/H+ -antiporter genes localized on the vacuolar (NHX1 to NHX3) and plasma membrane (SOS1). Melatonin effectively decreases the accumulation of lipid peroxidation products in potato leaves in the whole range of concentrations studied. A melatonin-induced dose-dependent increase in Fv/Fm together with a decrease in uncontrolled non-photochemical dissipation Y(NO) also indicates decreased oxidative damage. The observed protective ability of melatonin was unlikely due to its influence on antioxidant enzymes, since neither SOD nor peroxidase were activated by melatonin. Melatonin exerted positive effects on the accumulation of water-soluble low-molecularweight antioxidants, proline and flavonoids, which could aid in decreasing oxidative stress. The most consistent positive effect was observed on the accumulation of carotenoids, which are well-known lipophilic antioxidants playing an important role in the protection of photosynthesis from oxidative damage. Finally, it is possible that melatonin accumulated during pretreatment could exert direct antioxidative effects due to the ROS scavenging activity of melatonin molecules.